Power automate : a guide to power automate desktop. (Packt Publishing, 2023)
The demand for the Microsoft Power Automate platform is rapidly increasing, making it the top choice for medium-to-large companies, alongside PowerApps. This course is divided into beginner, intermediate, expert, and advanced levels for ease of learning. The topics covered in each of the levels are as follows: Introduction: Discover Power Automate Desktop, its robust features, strategies for success, course overview, and valuable reference materials. Beginner Level: Master the creation of fundamental flows, manipulating files and folders, handling text and dates, and leveraging email (Outlook) within your flows. Intermediate Level: Enhance your flows with user inputs, message boxes, advanced conditions, variables, loops, flow action controls, Excel integration, and automating applications through UI automation. Expert Level: Automate web activities using browser automation and recorders, execute database actions through HTTP, extract data from PDF files using OCR, and seamlessly integrate with cloud-based flows. Advanced Level: Achieve system automation, execute CMD actions, script actions with Python and PowerShell, and explore workstation actions for advanced workflow capabilities. If you are eager to learn and master Microsoft Power Automate Desktop, this comprehensive video course is tailored specifically for you. What You Will Learn Learn to use Power Automate Desktop to automate any routine task Learn to manipulate folders, files, text fields, and more when automating a task Learn to execute, share, and manage your Power Automate Desktop flows Understand how to create sophisticated logic in automating your tasks, with conditionals, loops, and variables Learn to retrieve email messages from Outlook Learn to use UI automation and browser automation Audience This video course is designed for individuals who aspire to reclaim their time by automating tasks on their desktop or the web. It is suitable for anyone looking to integrate automation into various processes, including business operations. Whether you are eager to master automation or specifically interested in Robotic Process Automation (RPA) features, this course is tailored to meet your needs. It is also ideal for automation and RPA enthusiasts, as well as Power Automate Cloud users who wish to expand their knowledge to include Power Automate Desktop. About The Author HHN Automate Book Inc.: Henry Habib is a seasoned manager at a leading management consulting firm. He leverages his expertise to provide counsel on growth strategy, operation, and analytics to Fortune 500 companies. With a strong background in implementing data-driven solutions, Henry has a proven track record of making an impact in organizations of all sizes. He strongly advocates for no-code application development in business and deploys such solutions for his clients. These solutions are not only easier to understand but also quicker to implement. In addition to his consulting work, Henry is a dedicated professor who takes pleasure in guiding students toward success in various fields, ranging from case interviews to no-code application development and automation. His courses are designed to be engaging and informative, and he is always available to assist students in mastering challenging concepts.